International Regulations and Guidelines on Transboundary Salmon Stocks: Case Study of the Tana River - Dahl, Irene Vanja (Arctic Review on Law and Politics, 2020)
The year 2019 was “the international year of the salmon” (IYS). The overarching aim was “to inform and stimulate outreach and research that aspires to establish the conditions necessary to ensure the resilience of salmon and people throughout the Northern Hemisphere;” further, to bring people together, share and develop knowledge, raise awareness and take action. This article is intended as a contribution to this goal. The article discusses how international law: the Law of the Sea Convention, the Convention on Biological Diversity and the Convention for the Conservation of Salmon in the North Atlantic Ocean relate to conservation and management of wild salmon. The article has a special focus on bilateral cooperation on salmon stocks in boundary/transboundary rivers, and using as a case study the Tana river in Norway and Finland.